Intercultural Learning: Teachers' Perspectives on the Influence of Intercultural Education on Students' Competence - Ameti, Makfirete; Zenki-Dalipi, Arbresha; Agai, Arita; Adili, Bujar (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
Intercultural education is an important dimension for both teachers and students in their personal and professional development. This research explored the primary school teachers’ views on how intercultural education shapes students' intercultural competence. A 12-item scale from Bedeković’s (2011) Survey Questionnaire (SQ) was administered to 217 primary school teachers in the Republic of North Macedonia. Statistical analyses using T-tests and ANOVA revealed significant differences in teachers' perceptions based on school structure, gender, teaching experience, prior intercultural education and education level. Based on these findings, intercultural education should be further integrated into curricula to enhance students' intercultural competence and better equip teachers for diverse classrooms.